Sero-Prevalence of Bovine Foot and Mouth Disease in Selected Districts of Eastern Showa Zone, Oromia Regional State, Ethiopia. (Global Journal of Science Frontier Research, 2016)
A cross-sectional study was conducted from September 2014 to July 2015 with the objective of determining sero-prevalence of Foot and Mouth Disease (FMD) in cattle in selected districts of Eastern Showa Zone, Oromia Regional. Blood samples were collected from a total of 634 cattle at Export abattoir, Veterinary Clinics in and around Bishoftu town of Adaa district and Bull screening quarantine station in Adama. The study animals were selected by systematic random sampling and blood samples were collected from jugular vein using sterile vacutainer tube. The blood samples were submitted to the National Veterinary Institute (NVI), and the serum were harvested and processed by using 3ABC-ELISA technique. The current study indicated the overall sero-prevalence of bovine FMD was 10.88% and statistically there were differences (P=0.002) in sero positivity of FMD among animals from Abattoir, Veterinary clinic and Feedlot. The sero-prevalence was higher in animals tested from export abattoirs than those from Feedlot and Clinics.
Keywords: bovine; FMDV; sero-prevalence; ethiopia; 3ABC-ELISA